The role of overweight, obesity and exercise therapy on low-back pain - Zagórski, Karol; Kozik, Mateusz; Skalska-Dziobek, Nina; Małagocka, Weronika; Chybowska, Karolina; Naruszewicz, Maria; Midro, Aleksandra; Cetnarowski, Przemysław (Quality in Sport, 2024)
Introduction and purpose: Low back pain (LBP) is a leading cause of impairment worldwide and its occurrence is still growing. There are many modifiable risk factors contributing to developing LBP, especially obesity, smoking and physical work. In spite of a breakthrough in pharmacotherapy, lifestyle changes and exercise remain the primary prophylactic and treatment options. The aim of this paper was to summarize the data available in the literature and recent reports about the effect of obesity and overweight on LBP and the effectiveness of different exercise programs. Material and methods: The literature was reviewed in the PubMed database, GoogleScholar and the Embase database with the use of keywords. State of knowledge: Obesity and overweight measured by BMI and other indicators are associated with LBP. Waist circumference (WC), recommended by WHO to measure central obesity was found to increase the risk of chronic LBP by 30%, but a stronger correlation between obesity and LBP was found among the female population. Furthermore, there is low-to-moderate evidence that exercise therapy is superior to conservative treatment, when it comes to decreasing pain severity in low back pain. All in all, aerobic, Pilates, core strengthening and stabilization and flexibility exercises were effective in reducing pain with no significant differences between the particular types of training. Summary: The information gathered indicates that obesity and overweight are essential risk factors for LBP. Also, various forms of exercise therapy help patients decrease pain in chronic LBP, however, they should be prescribed individually including preference and fitness level to promote compliance.